1992
DOI: 10.1161/01.hyp.19.1.85
|View full text |Cite
|
Sign up to set email alerts
|

High calcium diet augments vascular potassium relaxation in hypertensive rats.

Abstract: The effects of increased dietary calcium on the development of hypertension and vascular smooth muscle responses were studied in spontaneously hypertensive rats and normotensive Wistar-Kyoto rats. Both hypertensive and normotensive animals were divided into two groups; the calcium content of the normal diet was 1.1% and that of the high calcium diet 3.1%. During the 12-week study, calcium supplementation significantly attenuated the increase in systolic blood pressure in the hypertensive rats but did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 32 publications
(25 reference statements)
3
7
1
Order By: Relevance
“…Just as Furspan and Bohr 210 observed lower levels of intracellular free calcium in lymphocytes from animals on high calcium diets, Porsti et al 183 reported lower levels of intracellular free calcium in platelets isolated from animals maintained on supplemental calcium diets. These favorable changes in intracellular calcium regulation may be related to increased Ca 2+ -ATPase activity.…”
Section: + -Atpasementioning
confidence: 95%
See 2 more Smart Citations
“…Just as Furspan and Bohr 210 observed lower levels of intracellular free calcium in lymphocytes from animals on high calcium diets, Porsti et al 183 reported lower levels of intracellular free calcium in platelets isolated from animals maintained on supplemental calcium diets. These favorable changes in intracellular calcium regulation may be related to increased Ca 2+ -ATPase activity.…”
Section: + -Atpasementioning
confidence: 95%
“…In a previous report, they noted that potassium-induced relaxation of mesenteric arterial rings was augmented by calcium supplementation in SHR. 183 Because ouabain was able to prevent the relaxation, the difference between diet groups was attributed to increased Na,K-ATPase activity. This outcome is consistent with the notion of a reciprocal relation between intracellular calcium and Na,KATPase activity; as intracellular calcium declines, Na,K-ATPase activity increases.…”
Section: Nak-atpasementioning
confidence: 99%
See 1 more Smart Citation
“…Milk is rich in minerals (Ca, K), which most probably also contribute to the antihypertensive effect. For example, the antihypertensive effect of Ca has been shown quite uniformly in SHR (25,56,57) . Active milk significantly improved the endotheliumdependent relaxation of mesenteric arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter atenolol administration was withdrawn 1 day before the rats were decapitated and exsanguinated. The blood samples were drawn into polystyrene tubes containing heparin (100units ml-') as anticoagulant for lymphocyte intracellular free calcium concentration ([Ca2+]) measurements, which were performed as previously described Wuorela et al, 1992). The hearts were removed and weighed, and the superior mesenteric arteries carefully excised and cleaned of adherent connective tissue.…”
Section: Introductionmentioning
confidence: 99%